Declining fertility and economic well-being: Do education and health ride to the rescue? - Klaus Prettner; David E. Bloom; Holger Strulik (Institute for the Study of Labor (IZA), 2012)
It is widely argued that declining fertility slows the pace of economic growth in industrialized countries through its negative effect on labor supply. There are, however, theoretical arguments suggesting that the effect of falling fertility on effective labor supply can be offset by associated behavioral changes. We formalize these arguments by setting forth a dynamic consumer optimization model that incorporates endogenous fertility as well as endogenous education and health investments. The model shows that a fertility decline induces higher education and health investments that are able to compensate for declining fertility under certain circumstances. We assess the theoretical implications by investigating panel data for 118 countries over the period 1980 to 2005 and show that behavioral changes partly mitigate the negative impact of declining fertility on effective labor supply.
urn:nbn:de:101:1-2012081412521
Keywords: I15; I25; J24; O47; 330; demographic change; effective labor supply; human capital; population health; economic growth; Fruchtbarkeit; Bevölkerungsentwicklung; Arbeitsangebot; Bildungsinvestition; Gesundheitsvorsorge; Theorie; Schätzung; Welt